2015
DOI: 10.18268/bsgm2015v67n3a11
|View full text |Cite
|
Sign up to set email alerts
|

Identification of diagenetic calcium arsenates using synchrotron-based micro X-ray diffraction

Abstract: In this work, we identify the type of calcium arsenates found in sediment samples from an aquifer located in Matehuala, San Luis Potosí, México. Sediments in contact with levels up to 158 mg/L of arsenic in neutral pH water were studied by X-ray diffraction, scanning electron microscopy coupled to energy dispersive X-ray analyses (SEM-EDS), and synchrotron based X-ray diffraction. Identification of these calcium arsenates by X-ray analysis has proved to be very difficult to achieve because the precipitates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
7
0
2
Order By: Relevance
“…Matehuala geology is represented by sedimentary marine rocks, which is part of the eastern physiographic province of the Sierra Madre Oriental [ 63 ]. Therefore, soils at the study area are largely dominated by either calcite or gypsum [ 16 , 44 , 64 ]. The stratigraphic sequence of Matehuala consists mainly of PreOxfordian, Upper Jurassic, and Cretaceous carbonated series, a little portion of Tertiary volcanic rocks that cover the city, and Quaternary alluvial material deposited on the Matehuala valley [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Matehuala geology is represented by sedimentary marine rocks, which is part of the eastern physiographic province of the Sierra Madre Oriental [ 63 ]. Therefore, soils at the study area are largely dominated by either calcite or gypsum [ 16 , 44 , 64 ]. The stratigraphic sequence of Matehuala consists mainly of PreOxfordian, Upper Jurassic, and Cretaceous carbonated series, a little portion of Tertiary volcanic rocks that cover the city, and Quaternary alluvial material deposited on the Matehuala valley [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cycles of dissolution and precipitation of secondary arsenate minerals formed in soil after irrigation may also account for the accumulation of As in the topsoil and the vertical migration of As. Highly soluble arsenate minerals, such as haidingerite (CaHAsO 4 ·H 2 O; pk sp = 10 −4.79 ) and pharmacolite (CaHAsO 4 ·2H 2 O; pk sp = 10 −4.68 ), in addition to guerinite (Ca 5 H 2 (AsO 4 ) 4 ·9H 2 O; pk sp = 10 −30.69 ) have been found in the old abandoned smelter in Matehuala, as a result of the precipitation of As in a calcium-rich environment [ 64 , 66 , 67 ]. Previous studies have shown that As is highly soluble in water, and the more gypsum the soil contains, the lower the solubility of As, while higher calcite results in higher dissolution [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Para Ca 5 H 2 (AsO 4 ) 4 .nH 2 O con n = 9 para guerinita. Las fases identificadas en este trabajo concuerdan con las fases identificadas por Castillo et al (2015), quien identificó guerinita, haidingerita y farmacolita en muestras de suelos contaminados con arseniatos de calcio recolectados en Matehuala (Castillo et al 2015). La obtención de distintas fases de arseniatos de calcio en la síntesis 1 y 2 podría deberse a las diferencias de pH al comienzo de los experimentos (Fig.…”
Section: Discussionunclassified
“…En ambientes naturales e impactados, la identificación inequívoca de arseniatos de calcio ha demostrado, sin embargo, ser muy difícil de llevar a cabo (Ondrus et al 1997, Donahue y Hendry 2003, Onac et al 2007, Pantuzzo y Ciminelli 2010, Martínez-Villegas et al 2013, Castillo et al 2015) debido a la presencia de variados y diferentes arseniatos de calcio en muestras compuestas principalmente por otros minerales primarios (Ondrus et al 1997, Donahue y Hendry 2003, Onac et al 2007, Pantuzzo y Ciminelli 2010, Martínez-Villegas et al 2013, Castillo et al 2015. Aunado a la falta de reproducibilidad y ambigüedad de patrones de difracción de fases puras de arseniatos de calcio que no empatan con alguna fase conocida (Myneni et al 1997, Bothe y Brown 1999a, 1999b.…”
Section: Introductionunclassified
“…The ICP-OES measurements were performed by dissolving with concentrated HNO 3 and HCl the VA powder in a proportion of 0.1 g of VA in 10 mL (1:100 w/v) [15]. The equipment used was an ICP-OES brand Varian model 738 ES with the torch placed at the axial position and nebulizer flow of 0.75 L min −1 .…”
Section: Methodsmentioning
confidence: 99%